LOCUS: um sistema de localização geográfica através de referências espaciais indiretas - Ligiane Alves de Souza (2005)
An indirect spatial reference is any textual element used to identify places, without the use of spatial or geographic coordinates. Place names, urban addresses, postal area codes, and telephone numbers are examples of indirect spatial references. A gazetteer is a dictionary of place names. Its purpose is to supply the actual spatial location of indirect geographic references. In the recent past, some digital gazetteers have been developed to support geographic information retrieval initiatives and to enhance georeferencing applications. This dissertation presents Locus, a spatial locator system based on indirect geographic references. Locus includes a digital gazetteer, which was modeled in accordance to an ontology, the ontology of places. With this, the Locus gazetteer has become more elaborated and powerful than other currently available gazetteers. In the creation of Locus initial contents, data sources at the urban, regional, and national levels were employed, including the Brazilian postal company, the Brazilian telecommunications agency, and the local government for the city of Belo Horizonte. Furthermore, 29.139 place names were added, after being collected semiautomatically from Web sources using a data extraction by example mechanism. This dissertation also includes an evaluation of the potential use of Locus in a geographic information retrieval context, and proposes further applications in various fields, using either an interactive interface or Web services.